Performance and egg quality characteristics of layers fed diets with varied energy levels (2015)
This study was carried out to determine the effect of feeding varied energy level diets with balanced crude protein on the performance and egg quality characteristics of laying birds. One thousand two hundred (1200) Isa-Brown laying birds were allocated to four different diets in a completely randomized design. Diets 1, 2, 3, and 4 had 2500kcal/kg, 2600kcal/kg, and 2700kcal/kg and 2650kcal/kg energy respectively, with the study lasting 10 weeks. Data were collected on feed intake, egg production, egg weight, length, and width, yolk depth, length, and width, albumen width, length and depth, shell thickness and performance of laying birds fed the different diets. Results indicate that laying birds fed with 2,500kcal/kg performed better. The feed intake was highest and egg production also was highest without compromising the internal and external egg qualities. This gives an indication that adequate feed intake of balanced diet with moderate energy to a large extent will enhance better performance.